"Ik ben zoo diep gezakt door deze oorlog": Opvattingen over diefstal bij verdachten, reclasseerders en de Nederlandse rechterlijke macht, 1935-1949 - Jan Julia Zurné (TSEG - The Low Countries Journal of Social and Economic History, 2024)
During the German occupation of the Netherlands in the 1940s, crime rates for petty theft rose considerably. As a result of shortages, forced labor, unemployment and war damages, many citizens resorted to property crime. Those who were caught, were in majority sentenced within the Dutch judicial system, by Dutch magistrates, most of whom had no pro-German beliefs. This article explores how suspects, judges and probation officers referred to the occupation circumstances during the judicial process. All three types of actors saw how these circumstances could lead to theft. However, pre-existing notions of property and its defense were not radically questioned during the occupation. The (implicit) expectation was that the harmful consequences of the Second World War would be of a temporary nature.